Product Differentiation and Organizational Competitiveness: A Case of Amstus Polymer Packaging Limited, Namanve - Douglas Enock Higaye (Uganda Christian University, 2025)
The study aimed at posing the distinguishing relationship between product differentiation and organizational competitiveness. We used Amstus polymer packaging limited located in Namanve as our case study. When we dig deep in the highly competitive polymer sector, we see very many businesses coming up so to be able to take over the rivals in the market. Being guided the Porter’s Generic Strategies of cost leadership, focus and differentiation, the conducted study enabled the researcher to know how the different attributes of differentiation such as quality, branding and also the customer image influence the organizational competitiveness estimated in terms of market growth, brand recognition and also customer loyalty. A descriptive study method was employed where 90 questionnaires were issued out and got response of 73 questionnaires. This information was gathered through structured questionnaires and complemented it with thematic analysis for qualitative responses. The end results of the survey showed that the increased customer loyalty bridges a gap between the product uniqueness and the increased Organizational competitiveness. The different aspects of the product uniqueness measured in terms of innovative packaging, quality assurance and branding significantly create a positive relationship to achieve the competitiveness in terms of market share and sales growth. Moreover the product differentiation created more firm’s resilience and adaptability in response to the pressure of rivals and the change in tastes and needs of the customers. The survey ended that product uniqueness incorporated with strong customer loyalty is a critical driver of sustainable competitive advantage to the firm. It recommends the continuous product innovations so as to be able to be at the top of the market dynamics and be at the top of their rivals.